REVIEW OF BIOLOGICAL ACTIVITIES OF HYDRAZONES - Ali, Md. Rahmat; Marella, Akranth; Alam, Md. Tauquir; Naz, Ruksar; Akhter, Mymoona; Shaquiquzzaman, Md.; Saha, Rikta; Tanwar, Omprakash; Alam, Md. Mumtaz; Hooda, Jyoti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Hydrazones possess an azomethine –NHN=CH group and are considered as derivatives of aldehydes and ketones in which the oxygen atom has been replaced by the NNH2 functional group. These are widely studied molecules owing to their ease of preparation and diverse pharmacological potential. This has led researchers to synthesize different heterocyclic compounds bearing hydrazones. Medicinal chemists across the world have done immense work on hydrazones and developed agents with better activity and low toxicity profiles. Following different synthetic protocols and through proper SAR studies differently substituted hydrazones have been developed and found to be active against different pharmcological targets. They are known to possess different biological activities viz. antimicrobial, antiinflammatory, anticancer, antimalarial etc. These observations have been guiding for the development of new hydrazones that possess varied biological activities. The review aims at highlighting the diverse biological activities of hydrazones.Key words: Azomethine, Hydrazones, Pharmacological Potential